PENERAPAN PSAK NO. 30 TENTANG PERLAKUAN AKUNTANSI SEWA AKTIVA TETAP PADA PT. SINAR KARYA MEGA PERSADA - Pangkerego, Revine Marni; Budiarso, Novi (Universitas Sam Ratulangi, 2015)
Companies in the course of its business relative to lease equipment to run its operations rather than having to buy new equipment with the aim of minimizing costs. For the PT. Sinar Karya MegaPersada engaged in construction business and has opted to rent some equipment fixed assets in the form of heavy equipment as additional business to earn more income. Often the records maintained by the company is not in accordance with PSAK No. 30 of the lease of fixed assets. The purpose of this study to determine the accounting treatment applied to the PT. Sinar Karya Mega Persada is already in line with PSAK No. 30. The method used is descriptive study. The results showed lease accounting treatment of fixed assets using operating leases where the end of the lease, the equipment remains the property of the lessor in this case PT. Sinar KaryaMega Persada. The Company has not fully follow accounting standards in accordance with PSAK NO. 30 on leases of fixed assets. Head of the company should consistently apply the lease accounting treatment of fixed assets in accordance with PSAK No. 30, to be more accurate financial reporting.